Mathematics Learning Outcomes of Student using The Matter of Operations Numbers Edutainment Fractions - Analisa Fitria (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2017)
The purpose of this study was to determine the results of students' mathematics learning by using edutainment in operating material fractions in grade VII MTsS Babussalam Kumai academic year 2016/2017. In the implementation of this edutainment methods there are several obstacles, among them students not accustomed to using edutainment methods, so that students are confused how to implement it. The results of students' mathematics learning by using edutainment in operating material fractions in grade VII MTsS Babussalam Kumai 2016/2017 school year are at very high qualification and high, ie 80% of the students have acquired in accordance with KKM value ≥ 70. Key Words: teaching methods, mathematics, edutainment, fractions